Plant extracts, isolated phytochemicals, and plant-derived agents which are lethal to arthropod vectors of human tropical diseases - A review - Pohlit, Adrian Martin; Rezende, Alex Ribeiro; Lopes Baldin, Edson Luiz [UNESP]; Lopes, Norberto Peporine; De Andrade Neto, Valter Ferreira (Thieme, 2011)
The recent scientific literature on plant-derived agents with potential or effective use in the control of the arthropod vectors of human tropical diseases is reviewed. Arthropod-borne tropical diseases include: amebiasis, Chagas disease (American trypanosomiasis), cholera, cryptosporidiosis, dengue (hemorrhagic fever), epidemic typhus (Brill-Zinsser disease), filariasis (elephantiasis), giardia (giardiasis), human African trypanosomiasis (sleeping sickness), isosporiasis, leishmaniasis, Lyme disease (lyme borreliosis), malaria, onchocerciasis, plague, recurrent fever, sarcocystosis, scabies (mites as causal agents), spotted fever, toxoplasmosis, West Nile fever, and yellow fever. Thus, coverage was given to work describing plant-derived extracts, essential oils (EOs), and isolated chemicals with toxic or noxious effects on filth bugs (mechanical vectors), such as common houseflies (Musca domestica Linnaeus), American and German cockroaches (Periplaneta americana Linnaeus, Blatella germanica Linnaeus), and oriental latrine/blowflies (Chrysomya megacephala Fabricius) as well as biting, blood-sucking arthropods such as blackflies (Simulium Latreille spp.), fleas (Xenopsylla cheopis Rothschild), kissing bugs (Rhodnius Stål spp., Triatoma infestans Klug), body and head lice (Pediculus humanus humanus Linnaeus, P. humanus capitis De Geer), mosquitoes (Aedes Meigen, Anopheles Meigen, Culex L., and Ochlerotatus Lynch Arribálzaga spp.), sandflies (Lutzomyia longipalpis Lutz & Neiva, Phlebotomus Loew spp.), scabies mites (Sarcoptes scabiei De Geer, S. scabiei var hominis, S. scabiei var canis, S. scabiei var suis), and ticks (Ixodes Latreille, Amblyomma Koch, Dermacentor Koch, and Rhipicephalus Koch spp.). Examples of plant extracts, EOs, and isolated chemicals exhibiting noxious or toxic activity comparable or superior to the synthetic control agents of choice (pyrethroids, organophosphorous compounds, etc.) are provided in the text for many arthropod-vectors of tropical diseases. © Georg Thieme Verlag KG Stuttgart New York.
Keywords: acaricide; biotechnology; botanicals; essential oils; insecticidal and larvicidal plants; natural products; phytochemicals; plant extracts